Neutronics performance improvement based on the small lead-based fast reactor SLBR-50 - Zhao, Chen; Lou, Lei; Zhang, Bin; Zhou, Bingyan; Wang, Lianjie; Peng, Xingjie (Frontiers in Energy Research, 2022)
Design of high-performance lead-based fast reactor has already become a hotspot in the advanced reactor system. Research of the neutronics performance improvement is presented based on the small lead-based fast reactor SLBR-50. Parameter sensitivity analyses are conducted, including height-diameter ratio(H/D), reflector assembly arrangement, pitch-diameter ratio(P/D) in fuel assembly, fuel material and fuel enrichment partitioning. Numerical results of eigenvalue in burnup procedure, assembly power distribution and energy spectrum are analyzed with the Monte-Carlo code RMC. These results provide influences of these design parameters in quantity and the neutronics performance can be improved with parameter optimization.